1996
DOI: 10.1111/j.1365-2672.1996.tb03245.x
|View full text |Cite
|
Sign up to set email alerts
|

Hemicellulose‐degrading bacteria and yeasts from the termite gut

Abstract: Termites play a major role in the recycling of photosynthetically fixed carbon. With the aid of their symbiotic intestinal flora, they are able to degrade extensively wood constituents such as cellulose and hemicellulose. Nevertheless, the microbial species involved in the degradation of hemicelluloses are poorly defined. The purpose of this paper was to examine the microflora involved in hemicellulose degradation. Different aerobic and facultatively anaerobic bacteria and yeasts were isolated using xylan, ara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
91
0
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(100 citation statements)
references
References 32 publications
7
91
0
2
Order By: Relevance
“…On the other hand, in an extensive survey of the 16S rDNA clones of the gut microbial community of a lower termite Reticulitermes speratus 17,18,32) , we failed to detect a 16S rDNA sequence affiliated to Paenibacillus. There are two reports about the isolation of Paenibacillus from lower termites 35,42) . One report is on a xylanolytic Paenibacillus macerans and the other, a cellulolytic Paenibacillus sp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, in an extensive survey of the 16S rDNA clones of the gut microbial community of a lower termite Reticulitermes speratus 17,18,32) , we failed to detect a 16S rDNA sequence affiliated to Paenibacillus. There are two reports about the isolation of Paenibacillus from lower termites 35,42) . One report is on a xylanolytic Paenibacillus macerans and the other, a cellulolytic Paenibacillus sp.…”
Section: Discussionmentioning
confidence: 99%
“…A large number of lignocellulose decomposers that contained novel species have been isolated from the gut of termites including soil-feeders 26,35,42) . However, to our knowledge, this is the first report of the isolation and characterization of an alkaliphile from the termite gut.…”
Section: Discussionmentioning
confidence: 99%
“…Based on physiological characteristics using a microbial identification system BIOLOG, Mankowski & Morrell (2004) (Schäfer et al, 1996). Schäfer et al (1996) cultured 35 yeast isolates from the intestinal contents of termite species, Zootermopsis nevadensis and Neotermes castaneus, but the authors reported presence of only 15 yeast strains, as their enzymatic activity were significant to the study. These phenotypes were related to the genera Candida, Sporothrix, Pichia and Debaryomyces.…”
Section: Cryptococcus Flavescensmentioning
confidence: 99%
“…Furthermore, due to production of several enzymes, some yeast species, e.g. found in the gut of termites (Schäfer et al, 1996;Molnar et al, 2004) and beetles (Suh et al, 2003), are able to degrade hemicelluloses that are being the main carbohydrates of herbivorous diet, and also detoxify toxins that can appear in the feed. The possibility cannot b e e x c l u d e d t h a t s o m e y e a s t s h a r b o u r i n g GIT of herbivorous animals may produce extracellular enzymes (e.g.…”
Section: Role Of Yeasts In Gitmentioning
confidence: 99%
“…For example, Actinobacteria associated with termites assist in nutrient acquisition from a diversity of polysaccharides including cellulose (Pasti and Belli, 1985;Watanabe et al, 2003) and hemicelluloses (Schäfer et al, 1996). Proteobacteria associated with insects are also involved in carbohydrate degradation (Delalibera et al, 2005), and can be involved in provisioning other nutrients such as amino acids (Moran and Baumann, 2000) and nitrogen (PintoThomás et al, 2009).…”
Section: Introductionmentioning
confidence: 99%